The Prevalence of Using Traditional, Complementary, and Integrative Medicine by Patients with Epidermolysis Bullosa - Mohammad Mahdi Parvizi; Nasrin Saki; Ehsan Amiri-Ardekani; Parisa Ahmadfard; Mehdi Pasalar (Traditional and Integrative Medicine)
Epidermolysis bullosa (EB) is an inherited disease that causes widespread symptoms characterized by extreme epithelial fragility. This study examined traditional, complementary, and integrative medicine (TCIM) usage among EB patients referred to clinics at Shiraz University of Medical Sciences between 2019 and 2020. We enrolled the patients with EB whose diseases were approved by a dermatologist and registered in the dermatology department and Molecular Dermatology Research Center affiliated with Shiraz University of Medical Sciences, Shiraz, Iran.  A researcher-made data gathering form, including knowledge, beliefs, practice, and the experience of the safety of TCIM, was used to collect the data. Interviews were done by phone calls, and oral consent was obtained from patients or their parents. Overall, 68 patients were included in this study. In this regard, 79.4% of the patients used TCIM by themselves or their families to manage EB. Approximately, half of the patients were not aware of the effects of the herbal medicines they used. Among medicinal plants, chicory (20.6%), thyme (16.2%), and Persian cornflower (14.7%) had the most consumption. More than half of these patients believed that medicinal plants were a less harmful treatment, and 48.5% considered them effective. In conclusion, the study revealed high medicinal plant usage among EB patients, but limited knowledge about their effectiveness. Public awareness about the benefits and risks of these remedies needs to be increased.